Analisis Peran Pemerintah Daerah dalam Penyelesaian Konflik Agraria (Studi Kasus Konflik Antara PT. PP. London Sumatra dengan Masyarakat di Kabupaten Bulukumba) - Nur Azizah Raja (GOVERNMENT : Jurnal Ilmu Pemerintahan, 2019)
This study aimed to know and analyze the role of local government especially the local govern-ment of Bulukumba Regency, in the process of settling the agrarian conflict between PT. PP. London Sumatra and the civil society in Bulukumba Regency and to know the factors that caused the people to resist an extension of PT. PP. London Sumatra’s Rights to Exploit in Bulukumba Regency that will end in the next 2023. Type of research used in this research is de-scriptive with qualitative techniques, which will provide a clear and factual overview about the role of local government in the process of settling the agrarian conflict. The results of this study indicate that: 1) The role of local government especially the local government of Bulukumba Regency, in the process of settling the agrarian conflict between PT. PP. London Sumatra and the civil society in Bulukumba Regency is by making an attempt to conciliation and to form a team of complete conflicts. 2) The factors that caused the people to resist an extension of PT. PP. London Sumatra’s Rights to Exploit in Bulukumba Regency affected by two things that are the status of conflict is still unfinished and minimize contributions of PT. PP. London Sumatra for community and general local construction.